Alterations of the Gut Microbiome Composition and Lipid Metabolic Profile in Radiation Enteritis - Li, Yiyi; Yan, Hongmei; Zhang, Yaowei; Li, Qingping; Yu, Lu; Li, Qianyu; Liu, Cuiting; Xie, Yuwen; Chen, Keli; Ye, Feng; Wang, Kai; Chen, Longhua; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Abstract Radiation enteritis (RE) is a common complication in cancer patients receiving radiotherapy. Although studies have shown the changes of this disease at clinical, pathological and other levels, the dynamic characteristics of local microbiome and metabolomics are hitherto unknown. We aimed to examine the multi-omics features of the gut microecosystem, determining the functional correlation between microbiome and lipid metabolites during RE activity. By delivering single high-dose irradiation, a RE mouse model was established. High-throughput16S rDNA sequencing and global lipidomics analysis were performed to examine microbial and lipidomic profile changes in the gut microecosystem. Spearman correlation analysis was used to determine the functional correlation between bacteria and metabolites. Clinical samples were collected to validate the above observations. During RE activity, the intestinal inflammation of the mice was confirmed by typical signs, symptoms, imaging findings and pathological evidences. 16S datasets revealed that localised irradiation dramatically altered the gut microbial composition, resulting in a decrease ratio of Bacteroidetes to Firmicutes. Lipidomics analysis indicated the remarkable lipidomic profile changes in enteric epithelial barrier, determining that glycerophospholipids metabolism was correlated to RE progression with the highest relevance. Spearman correlation analysis identified that 5 bacteria-metabolite pairs showed the most significant functional correlation in RE, including Alistipes-PC(36:0e), Bacteroides-DG(18:0/20:4), Dubosiella-PC(35:2), Eggerthellaceae-PC(35:6), Escherichia-Shigella-TG(18:2/18:2/20:4). These observations were partly confirmed in human specimens. Our study provided a comprehensive description of microbiota dysbiosis and lipid metabolic disorders in RE, suggesting strategies to change local microecosystem to relieve radiation injury and maintain homeostasis.